PERTANGGUNGJAWABAN DIREKSI PT. ANEKA TAMBANG ATAS PENUNJUKAN BUTIK PENJUALAN EMAS YANG MERUGIKAN PEMBELI (Studi Kasus: Putusan Tingkat Kasasi Nomor 1666/K/Pdt/2022) - Adinda Yasmin Fauziah (2024)
Gold buying and selling activities in Indonesia are activities that are favored by the community. Although buying and selling activities are one form of agreement that has been regulated in the Indonesian Law Code, in practice there is still an arbitrariness in the gold buying and selling activities carried out by one of the gold boutiques owned by PT Aneka Tambang which causes losses to the Buyer. Buyers' rights in gold buying and selling activities must be protected in order to achieve a sense of security in society, including their right to clear accountability. Subject matter: (1) How is the consideration of the judge in deciding the case between Budi Said and PT Antam for the loss caused by the gold boutique to the Buyer? (2) How should the Board of Directors be responsible for the appointment of a gold boutique that causes loss to the Buyer? To answer these problems, normative juridical research is conducted using secondary data and analyzed normatively qualitatively. The conclusions of this study are (1) The judge decided that the Board of Directors of PT Antam is jointly and severally liable for the losses incurred by employees under its supervision based on the provisions of Article 1367 of the Civil Code based on the legal relationship between the Gold Boutique, Employees, and PT. Antam with the Buyer; (2) Directors who are declared negligent must be jointly and severally liable based on Article 97 paragraph 2 of the Company Law, based on the Civil Code, the default caused by the Antam Gold Boutique obliges the Company to be responsible for compensation as in Article 1243, in the context of a tort, the Board of Directors must be responsible for the mistakes of its employees as in Article 1367 of the Civil Code.